Perceived stress and its association with body fat percentage among academic and administrative employees in Universiti Teknologi MARA Pahang - Mohamed Kassim, Nur Atikah; Abdul Razak, Fatin Aqilah; Shahudin, Nurul Nadiah; Isa, Kalam Azad; Ab Razak, Rozella; Syed Hamzah, Sharifah Raidah (GADING Journal for the Social Sciences, 2025)
Stress has been identified as a risk factor for high blood pressure, cardiovascular disease, and cancer. Recent research has suggested that body composition is essential in determining health and disease. However, the influence of stress on body composition among higher institutional staff remains to be determined. This study aimed to compare perceived stress and body fat percentage levels between two categorical groups. Furthermore, this study investigated the correlation between stress and body composition among academicians and administrators in Universiti Teknologi MARA Pahang, Malaysia. One hundred and forty (N=140) participants were involved in this study. They were divided into two categorical groups, which were referred to as "academicians" and "administrators." A demographic profile, the Perceived Stress Scale-10, and body fat percentage were obtained to assess the stress level and participants' body composition. Independent t-test results suggested that academicians more stressed than the administrators. In terms of body fat percentage, neither group demonstrated a statistically significant difference in results. Additionally, pairwise correlation demonstrated a statistically significant positive relationship between fat percentage and stress level (p < 0.05, r = 0.235). Tracking body composition and perceived stress can provide valuable insights into the health and well-being of higher education staff. This is to facilitate the implementation and facilitation of future initiatives involving the staff and act as an aid to regulate their performance aim.